Shortage of mitogen-activated protein kinase is responsible for resistance to AP-1 transactivation and transformation in mouse JB6 cells - Huang, Chuanshu (National Academy of Sciences, 1998)
The JB6 mouse epidermal cell system, which includes tumor promotion-sensitive (P(+)) and tumor promotion-resistant (P(−)) cells, is a well-established and extensively used cell culture model for studying the mechanism of late-stage tumor promotion. Tumor promoters, such as 12-O-tetradecanoylphorbol 13-acetate (TPA) or epidermal growth factor (EGF), induce high levels of activator protein 1 (AP-1) activity and large, tumorigenic, anchorage-independent colonies in soft agar at a high frequency in JB6 P(+) cells, but not in JB6 P(−) cells. We report here a molecular explanation for the defect in the AP-1 activation and promotion-resistant phenotype of P(−) cells. We demonstrate that the lack of AP-1 activation and cell transformation responses to TPA and EGF in P(−) cells appears attributable to the low level of mitogen-activated protein kinase (MAPK) (extracellular signal-regulated protein kinase, Erk) in these cells. TPA and EGF induce transactivation of AP-1 activity in P(+) cells but not in P(−) cells. Nonphosphorylated forms and TPA- or EGF-induced phosphorylated forms of Erks (Erk1 and Erk2) in P(−) cells were much lower than those in P(+) cells. Stable transfection of wild-type MAPK (Erk2) into P(−) cells restored its response to TPA and EGF for both AP-1 activation and cell transformation. These results suggest that the shortage of MAPK (Erk1 and Erk2) appears to be an important contributor to the tumor promotion-resistant phenotype in JB6 cells.